WDR79 mediates the proliferation of non‐small cell lung cancer cells by regulating the stability of UHRF1. Issue 5 (7th March 2018) - Chen, Jieying; Sheng, Xunan; Ma, Hongchang; Tang, Zhengshan; Yang, Chao; Cao, Lanqin; Sun, Yang; Deng, Tanggang; Feng, Peifu; Hu, Bin; Wei, Dong; Liu, Jing; et al.
Abstract: WD repeat protein 79 (WDR79) is a member of the WD‐repeat protein family characterized by the presence of a series of WD‐repeat domains and is a scaffold protein that participates in telomerase assembly, Cajal body formation and DNA double strand break repair. Although previous studies have revealed that WDR79 is frequently overexpressed in non‐small cell lung cancer (NSCLC) and promotes the proliferation of NSCLC cells, the underlying mechanism responsible for WDR79‐mediated NSCLC proliferation is not fully understood. In this study, we report a novel molecular function of WDR79 that mediates NSCLC cell proliferation by controlling the stability of UHRF1. In the nucleus, WDR79 colocalized and interacted with UHRF1. As a result, overexpression of WDR79 stabilized UHRF1, whereas ablation of WDR79 decreased the level of UHRF1. Meanwhile, we showed that WDR79 can protect UHRF1 from poly‐ubiquitination‐mediated proteolysis, which facilitated the stabilization of UHRF1. We further demonstrated that WDR79 exerts a proliferation effect on NSCLC cells by stabilizing UHRF1. These findings reveal that WDR79 is a novel UHRF1 regulator by maintaining UHRF1 stability, and they also provide a clue as to how to explore WDR79 for potential therapeutic application in NSCLC.